Surgeons and preventative health: protocol for a mixed methods study of current practice, beliefs and attitudes influencing health promotion activities amongst public hospital surgeons - Stephen Barrett; Stephen Begg; Michael Kingsley (BMC, 2018)
Abstract Background The high prevalence of non-communicable diseases places significant demands on the healthcare system. As a result, hospitals are seeking to broaden their role to include more integrated health promotion. Strong leadership at different levels of the organisation is required for the successful integration of health promotion in hospital settings. The status of surgeons within healthcare affords them significant influence over clinical practice, and by extension, institutional policy and practice. The voice of this professional group is, however, absent from preventative health literature. The aim of this research is to identify which health promotion activities surgeons undertake, and to explore the attitudes of the profession towards health promotion activities. Methods A mixed methods study will be conducted, guided by the principles of sequential explanatory design. Quantitative results from a clinician survey will be followed by in-depth, semi structured interviews to explore findings in more depth through qualitative analysis. We will recruit from general and orthopaedic surgeons and registrars in a major tertiary hospital in a regional city in Australia (n ≈ 31). Data will be collected, independently coded and analysed using a qualitative descriptive approach. Quantitative and qualitative results will be merged during interpretation to provide complementary perspectives of interrelated contextual factors that influence health promotion activities amongst hospital surgeons. Discussion The depth of insight gained from these highly professionalised clinicians will offer a distinctive perspective on current practice, as well as the challenges of implementing effective health promotion into surgical practice. The findings from this research will assist in guiding strategy and policy at both clinical and institutional levels on health promotion planning and practice. Gaining insights from surgeons will strengthen the evidence base to assist the integration of health promotion into hospital practice.